Exploration of the Impact of Harsh Language in Kurdish Society on Social Media - Facebook: A Sociolinguistic Case Study - Bahra Salam HamaGharib; Aryan Sdiq Aziz; Nali Adham Gharib; Shabaz Abdalla (Engiscience Publisher, 2023)
The study explores the multifaceted realm of language within the Kurdish society. Employing a sociolinguistic perspective, the study meticulously examines horizontal elements such as environmental influences, social groups, values, and attitudes, alongside vertical elements including language variations across societal classes, literacy levels, demographics, and age groups. Recognizing language as a fundamental tool for comprehension and communication, the research emphasizes its pivotal role in human life and societal progress. The paper aims to investigate that language usage significantly influences relationships, either strengthening or straining them, necessitating careful consideration by language users. The study focuses on diverse facets, encompassing language applications, the role of slang, and the repercussions of its use in social media. Explicit language, particularly prevalent in online platforms, is scrutinized for its motivations and subsequent adverse effects on individuals and society. With a specific focus on slang, the paper seeks to validate this linguistic form and elucidate its informal impact on both senders and recipients, contributing to a comprehensive understanding of language dynamics in Kurdish society.